Full Thickness Skin Graft Procedure for Basal Cell Carcinoma : A Case Report: Poster Presentation - Case Report - Resident - PETER SALMON; Yuliana Hartono (Majalah Oftalmologi Indonesia, 2023)
Introduction : To present a case of basal cell carcinoma (BCC) of the right upper eyelid using a full thickness skin graft (FTSG) procedure Case Illustration : 69 year old woman with the main complaint of a lump on the upper right eye that has been getting bigger and bleeding more and more since 4 years ago. Examination revealed a tumor measuring 22mm x 12mm x 5mm, smooth surface of pearl-like nodules, talengectiasis, madarosis, palpebral retraction towards the medial canthus. The patient works as a farmer. Wide excision of the tumor and FTSG procedure was performed from the right infraclavicular area, histopathological results of basal cell carcinoma tumor. Discussion : BCC accounts for 90% of malignant eyelid tumors. The biggest risk factor for BCC is UV exposure. BCC rarely metastasizes but orbital invasion occurs in approximately 2%. This patient underwent an FTSG procedure. The graft was taken from the infraclavicular area. One of the key factors for graft success is revascularization of the graft area. Conclusion : FTSG procedure for BCC can give good results. The risk after the procedure is sometimes difficult to predict so that it can become difficult in graft attachment and even failure in attachment to the excision area can occur. This patient was under close observation due to a hematoma under the graft skin.